Slow hot-carrier cooling in halide perovskites : prospects for hot-carrier solar cells - Li, Mingjie (2020)
Rapid hot-carrier cooling is a major loss channel in solar cells. Thermodynamic calculations reveal a 66% solar conversion efficiency for single junction cells (under 1 sun illumination) if these hot carriers are harvested before cooling to the lattice temperature. A reduced hot-carrier cooling rate for efficient extraction is a key enabler to this disruptive technology. Recently, halide perovskites emerge as promising candidates with favorable hot-carrier properties: slow hot-carrier cooling lifetimes several orders of magnitude longer than conventional solar cell absorbers, long-range hot-carrier transport (up to ≈600 nm), and highly efficient hot-carrier extraction (up to ≈83%). This review presents the developmental milestones, distills the complex photophysical findings, and highlights the challenges and opportunities in this emerging field. A developmental toolbox for engineering the slow hot-carrier cooling properties in halide perovskites and prospects for perovskite hot-carrier solar cells are also discussed.